Edukasi Higiene Sanitasi dalam Upaya Pencegahan Scabies di Pondok Pesantren, Kabupaten Lamongan - Notobroto, Hari Basuki; Diyanah, Khuliyah Candraning; Pawitra, Aditya Sukma; Yudhastuti, Ririh; Adriyani, Retno; Sulistyorini, Lilis; Prasasti, Corie Indria; Azizah, R.; Lestari, Kusuma Scorpia; Sudarmaji, Sudarmaji; Dimjati Lusno, Muhammad Farid; Husnina, Zida; Puji Astuti, Ratna Dwi; Kusuma Wardani, Ratnaningtyas Wahyu; Arfiani, Novi Dian; Dhamayanti, Yeni; Saleh, Tania Ardiani; Naser, Mhd. Izzan; Jassey, Babucarr (Universitas Pahlawan Tuanku Tambusai, 2025)
Skin diseases such as scabies continue to pose significant health issues within pesantren (Islamic boarding schools) due to inadequate sanitation and low awareness among students regarding personal higiene. Scabies is highly contagious, transmitted through direct contact and the sharing of personal items. Therefore, there is a need for interventions, specifically educational programs, to enhance knowledge and awareness about sanitation and the prevention of scabies in pesantren. This activity aims to improve students understanding of environmental sanitation, personal higiene, and the prevention and control of scabies through educational outreach activities. This initiative was conducted using outreach and practical training methods for students at Pondok Pesantren Al Amin, Lamongan. Evaluation involved pre-tests and post-tests, comparing the results to measure the increase in participants' knowledge. The results was a noticeable improvement in students' knowledge, with the average score increasing from 84.1% on the pre-test to 91.6% on the post-test concerning personal higiene and environmental sanitation at the pesantren (p-value = 0.000). This educational activity successfully enhanced students' understanding of sanitation and health in the pesantren setting. Further approaches are necessary for the prevention and transmission of scabies.